2022
DOI: 10.3390/antiox11030497
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in Stem Cell Biology

Abstract: Nitric oxide (NO) is a gaseous biomolecule endogenously synthesized with an essential role in embryonic development and several physiological functions, such as regulating mitochondrial respiration and modulation of the immune response. The dual role of NO in embryonic stem cells (ESCs) has been previously reported, preserving pluripotency and cell survival or inducing differentiation with a dose-dependent pattern. In this line, high doses of NO have been used in vitro cultures to induce focused differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…NO is involved in the regulation of cell growth, survival, apoptosis, proliferation, and differentiation [56,64]. In healthy odontoblasts, eNOS [43,65], and in inflamed odontoblasts, iNOS and ONOO − [7] have been described.…”
Section: Discussionmentioning
confidence: 99%
“…NO is involved in the regulation of cell growth, survival, apoptosis, proliferation, and differentiation [56,64]. In healthy odontoblasts, eNOS [43,65], and in inflamed odontoblasts, iNOS and ONOO − [7] have been described.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, NO has been shown to play role in developmental and physiological processes, including floral transition, reaction to hypoxia, as well as immune and defense responses 4,2123 . Additionally, several lines of evidence have suggested that redox state plays an important role in stem cell homeostasis, including the key redox component RNS and reactive oxygen species (ROS) 2,6,2426 . NO and ROS are involved in controlling differentiation of embryonic stem cells in animals 2,27,28 and more recently, they have been shown to act as important signals in root and shoot stem cell systems of plants 3,6,7,25,29 .…”
Section: Mainmentioning
confidence: 99%
“…Second, the production of NO is known to play a role in the maintenance of pluripotency (reviewed in [ 100 , 101 ]). Indeed, low μM of NO have been shown to protect mESCs from death or differentiation following leukemia inhibitory factor (LIF) withdrawal, through a blocked caspase 3 activation, an upregulation of anti-apoptotic genes such as Bcl2 , and a downregulation of differentiation genes such as Brachyury or Gata4 (GATA Binding Protein 4) [ 102 ].…”
Section: Succinate As a Paracrine Effectormentioning
confidence: 99%